2020
DOI: 10.1186/s13568-020-00973-0
|View full text |Cite
|
Sign up to set email alerts
|

A candidate probiotic strain of Enterococcus faecium from the intestine of the crucian carp Carassius auratus

Abstract: In the present study, a Gram-positive bacterium was isolated from the intestine of healthy crucian carp Carassius auratus and named strain R8. It was initially identified as Enterococcus faecium according to its morphological, physiological and biochemical characteristics. Further identification by using 16S rRNA gene sequence analysis confirmed the R8 strain (Genbank accession no. MF928076) as E. faecium. Challenge and hemolysis experiments showed that the E. faecium R8 strain had no toxicity to the crucian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Similar results were found in previous studies of synbiotics on Japanese eel (Lee et al 2018;Park et al 2020), olive flounder, Paralichthys olivaceus (Hasan et al 2018), and Nile Tilapia, Oreochromis niloticus (Hassaan et al 2014;Dawood et al 2020). It has been suggested that if probiotic strains are not from a host, their survivability and effectiveness in colonising the host could be limited because their biological activities are most advantageous in their normal environment (Lazado et al 2010(Lazado et al , 2015Mao et al 2020). Our finding suggested that fish fed BSMOS may be more efficient than fish fed EFFOS, but this difference might have also resulted from differences in prebiotics.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found in previous studies of synbiotics on Japanese eel (Lee et al 2018;Park et al 2020), olive flounder, Paralichthys olivaceus (Hasan et al 2018), and Nile Tilapia, Oreochromis niloticus (Hassaan et al 2014;Dawood et al 2020). It has been suggested that if probiotic strains are not from a host, their survivability and effectiveness in colonising the host could be limited because their biological activities are most advantageous in their normal environment (Lazado et al 2010(Lazado et al , 2015Mao et al 2020). Our finding suggested that fish fed BSMOS may be more efficient than fish fed EFFOS, but this difference might have also resulted from differences in prebiotics.…”
Section: Discussionsupporting
confidence: 86%
“…Among the strains isolated from piauçu, ST9 E. faecium showed inhibition ability against Aeromonas hydrophila and Aeromonas jandaei, similar to the positive control with antibiotics. Inhibition ability against A. hydrophila, Pseudomonas aeruginosa, Enterococcus durans, Staphylococcus haemolyticus, Vibrio parahaemolyticus, and V. vulnificus has been reported for E. faecium (Dias et al, 2019;El-Jeni et al, 2016;Mao et al, 2020;Vieira et al, 2013). The genus Enterococcus contains some species with resistance to antimicrobial compounds and antibiotics through mutagenic processes (Pietro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The antagonistic potential of E. faecium has been reported against A. hydrophila, P. aeruginosa, A. veronii, Staphylococcus haemolyticus, Vibrio parahaemolyticus, and V. vulnifcus (Dias et al, 2019;Mao et al, 2020;Paixão et al, 2020b). Its ability is related to the capacity to release lactic acid, hydrogen peroxide, and bactericides, antimicrobial compounds that control pathogens, in addition to competing for specific space and binding sites in the intestinal tract (Ng et al, 2020;Paixão et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%